Síntese, sinterização em forno de micro-ondas e caracterização da Fe-Ni, PZT e do sistema multifuncional magnetoelétrico PZT/Fe-Ni - Hoyos, José Rodrigo Muñoz (2012)
The production of multifunctional magnetoelectric materials today is potentiated in the manufacture of particulate (0-3 connectivity) or multilayer (2-2 connectivity) composites comprising a phase with magnetic properties and another with piezoelectric properties. The magnetoelectric response of this type of material depends on factors such as the properties of each of the phases in the composite, the microstructure and the homogeneity of the mixture of phases. The topic of this dissertation is a study of powder synthesis by the Pechini method and of the microwave sintering of ceramic bodies made of magnetic materials such as nickel ferrite and ferroelectric materials such as lead zirconate titanate, as well as an evaluation of their ferromagnetic and ferroelectric properties. This study includes an evaluation of the influence of microwave sintering on the microstructural, ferroelectric and magnetoelectric properties of particulate composites of the PZT/Fe-Ni (80/20) system. To this end, the powders were synthesized by the Pechini method in solutions at different levels of pH in order to evaluate the effect of this parameter on their particle size. The structural and microestructural characterization indicated that crystalline powders of both PZT and Fe-Ni phases were obtained, with nanometric particle sizes which decreased as the pH of synthesis increased. Dense Fe-Ni, PZT and PZT/Fe-Ni ceramic bodies were obtained by microwave and conventional sintering and analyzed by XRD, SEM and EDS. Fe-Ni and PZT samples showing high phase density and integrity were characterized by magnetic and electric hysteresis cycles, which elicited the typical responses of ferroelectric and ferromagnetic materials. The magnetoelectric coupling coefficient of samples of PZT/Fe-Ni composites with densities of >90 % and adequate phase integrity showed a value of 0.7 mV/cmOe for the microwave sintered sample and of 2.2 mV/cmOe for the conventionally sintered sample.